35.3k views
4 votes
What is the answer for
6-3(n-2)=8-n

2 Answers

6 votes

Answer:

n = 2

Explanation:

6 - 3 (n - 2) = 8 - n

6 - 3n + 6 = 8 - n

12 - 3n = 8 - n

12 = 8 + 2n

4 = 2n

2 = n

n = 2

User Mirza Bilal
by
5.4k points
6 votes

Answer:

n=2

Explanation:

Simplify.

6−3(n−2)=8−n

6+(−3)(n)+(−3)(−2)=8+−n(Distribute)

6+−3n+6=8+−n

(−3n)+(6+6)=−n+8(Combine Like Terms)

−3n+12=−n+8

−3n+12=−n+8

Add n to both sides.

−3n+12+n=−n+8+n

−2n+12=8

Subtract 12 from both sides.

−2n+12−12=8−12

−2n=−4

Divide both sides by -2.

-2n/-2 = -4/-2

n=2

User Aquaraga
by
5.3k points